Struktur Teori Akuntansi dan Kualitas Informasi Keuangan Sektor Publik: Tinjauan Literatur - Susanty Ismail; Dita Aulia Buata; Mattoasi Mattoasi; Hartati Tuli (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The quality of financial information is a crucial element in ensuring accountability and transparency in public sector financial management. Various accounting reforms have been implemented to improve the quality of financial reporting; however, their effectiveness is largely influenced by the underlying structure of accounting theory. This study aims to examine the role of accounting theory structure in shaping the quality of financial information in the public sector. The method employed is a literature review of scholarly journals addressing accounting theory, financial information quality, accrual-based accounting, and public sector accounting standards. The analysis is conducted by categorizing the literature based on theoretical components, mechanisms of influence, institutional context, and the implications of financial reporting. The findings indicate that the structure of accounting theory, encompassing agency theory, accountability theory, and modern public management approaches, contributes to financial information quality through the adoption of accrual-based accounting, the strengthening of internal control systems, and enhanced reporting transparency. These contributions vary across countries and institutions depending on institutional capacity and governance quality. High-quality financial information has significant implications for improving public accountability and the effectiveness of decision-making. This study concludes that accounting theory structure plays a strategic role in enhancing the quality of public sector financial information.